Rocking the Bayan: PKS Strategy to Replace Golkar Party's Dominance in the 2019 Legislative Elections in Bandung Regency - Adiwilaga, Rendy; Qodir, Zuly; Rahman, Taufiqur (Journal of Governance, 2025)
The Partai Keadilan Sejahtera (PKS) in several regions in principle has significant differences with national achievements in terms of increasing electability. Although the national achievement stagnated at 7-8%, in Bandung Regency, PKS succeeded in disrupting the dominance of the Golongan Karya (Golkar) party, which for almost 20 years controlled Bandung Regency in both the executive and legislative realms. This is based on the fact that in 2019, PKS took second place in the legislative vote. This research uses Peter Schroder's political marketing strategy theory with two variables, namely offensive strategies (market expansion strategies and market penetration strategies) and defensive strategies (market defense strategies and market closing strategies). This research is also dissected with a qualitative approach, where data analysis is operated with a mixed method between unstructured interviews with PKS leaders in Bandung Regency and the use of secondary data collected from mass media and PKS official social media. The results showed that PKS was able to move to the second position of the legislative election vote because it managed to take advantage of several strategic moments ranging from the 212 Islamic Defense Action in the national realm to populist program campaigns such as lifetime driving licenses and tax-free motor vehicles and was agile in positioning itself to respond to the internal conflict of the Golkar party in Bandung Regency by then carrying Golkar cadres who left the party.